Petrochemical specialities of volcanic rocks in the South of Gornaya Shoria, Telbes region - V V Diakonov; E E Kotelnikov; A E Kotelnikov (RUDN Journal of Engineering Research, 2010)
Volcanic and subvolcanic rocks that compose Telbes paleovolcanic structure in Gornaya Shoria according to the results of chemical analyses belong to an integral volcano-plutonic association.